Use of RNA interference to investigate gene function in the human filarial nematode parasite Brugia malayi. - Aboobaker, A; Blaxter, M (2003)
We describe the successful use of the reverse genetic technique RNA interference (RNAi) to investigate gene function in the human filarial nematode parasite Brugia malayi. We used fluorescently labelled double stranded RNA (dsRNA) to demonstrate that 300 bp molecules are able to enter adult females in culture while they remain excluded from microfilariae (mf). We have developed an optimised microvolume culture system to allow the exposure of parasites to high concentrations of dsRNA for extended periods. Culturing of adult female parasites in this system for 24h does not significantly reduce parasite lifespan or mf release in culture. Three B. malayi genes, beta-tubulin (Bm-tub-1), RNA polymerase II large subunit (Bm-ama-1) and B. malayi mf sheath protein 1/mf22 (Bm-shp-1) were targeted by soaking adult female B. malayi in dsRNA complementary to these transcripts in the optimised culture system. Targeting of the two housekeeping genes Bm-tub-1 and Bm-ama-1 led to a reduction in the levels of their transcripts, as assessed by reverse transcriptase coupled PCR (RT-PCR), and resulted in parasite death in culture. In contrast, targeting of the Bm-shp-1 gene was not lethal to adult females in culture. A marked reduction in mf release was observed for shp-1 RNAi parasites compared to controls and in addition 50% of mf released did not have fully elongated sheaths. This "short" phenotype correlated with the loss of the stockpiled shp-1 transcript from developing mf in treated adult female gonads. From these data we conclude that RNAi may be a useful method for assessment of drug target potential of genes identified in filarial gene discovery projects.